Association between social participation and medical care utilization among rural older adults in China: a longitudinal study based on the CLHLS (2011–2018) - Dianrui Yao; Le Yang; Naoki Kondo (BMC Geriatrics)
Abstract Background There is limited understanding regarding the patterns and trajectories of social participation and their associations with medical care utilization among rural older adults. We aimed to investigate the patterns and trajectories of social participation and their associations with medical care utilization among rural older adults in China using longitudinal data. Methods In this longitudinal study, we used data from 1600 participants aged 60 years and above in the Chinese Longitudinal Healthy Longevity Survey (CLHLS). We included participants with social participation information in 2011 (T1) as the baseline and followed them up in 2014(T2) and 2018(T3). Latent profile analysis (LPA) and latent transition analysis (LTA) were employed to identify the latent classes of social participation and the transition probabilities between these classes. Multinomial logistic regression was used to examine the predictors of transitions, while a two-part model and cross-lagged model were utilized to clarify the longitudinal relationship between social participation and medical care utilization among rural older adults. Results Three social participation classes were identified by LPA: low, moderate, and high social participation. The high social participation class exhibited strong stability, with rare transitions to other classes. Subjective economic status, self-rated health, and the number of chronic diseases significantly predicted social participation transition patterns (P < 0.05). Regarding outpatient care utilization, social participation consistently predicted more frequent outpatient visits in all waves (P < 0.05) but was associated with higher outpatient expenses only at T3 (P < 0.05). However, no significant association was observed between social participation and inpatient care utilization. This finding was further supported by cross-lagged modeling, demonstrating significant effects of social participation on outpatient care utilization (β = 0.016 to 0.018, SE = 0.004, P < 0.001). Conclusions This research reveals the social participation dynamics in rural older adults and their effects on medical care utilization in China. Social participation can significantly promote outpatient care utilization among rural older adults. Targeted policy and practice are needed for those with low levels of social participation in rural areas.